2001
DOI: 10.1046/j.1365-2761.2001.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of European crustaceans with white spot syndrome virus (WSSV)

Abstract: Eight European marine and freshwater crustaceans were experimentally infected with diluted shrimp haemolymph infected with white spot syndrome virus (WSSV). Clinical signs of infection and mortalities of the animals were routinely recorded. Diagnosis was by direct transmission electron microscopy (TEM), DNA hybridization (dot‐blot and in situ hybridization) using WSSV probes and by PCR using WSSV specific primers. High mortality rates were noted between 7 to 21 days post‐infection for Liocarcinus depurator, Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 19 publications
4
53
0
2
Order By: Relevance
“…Within a decade, it has become a serious threat to the shrimp culture industry throughout Asia and Latin America (Hill 2002). WSSV also infects many other crustacean species from several regions of the world (Lo et al 1996, Chang et al 1998, Kasornchandra et al 1998, Wang et al 1998, Rajendran et al 1999, Corbel et al 2001, Hossain et al 2001, Sahul-Hameed et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Within a decade, it has become a serious threat to the shrimp culture industry throughout Asia and Latin America (Hill 2002). WSSV also infects many other crustacean species from several regions of the world (Lo et al 1996, Chang et al 1998, Kasornchandra et al 1998, Wang et al 1998, Rajendran et al 1999, Corbel et al 2001, Hossain et al 2001, Sahul-Hameed et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…It is a rod-shaped, double-stranded DNA virus affecting tissues of ectodermal and mesodermal origin in penaeids, and it results in mass mortalities. In addition, other crustaceans such as crabs, copepods, lobsters, prawns and krill act as asymptomatic carriers of the virus (Yu et al 1995, Flegel 1996, Supamattaya et al 1998, Rajendran et al 1999, Chen et al 2000, Corbel et al 2001. Dual infection of Penaeus monodon with WSSV and yellow head virus (YHV) , Sithigorngul et al 2000 has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a virus designated B2 that is morphologically similar to WSSV was described in Mediterranean crab Carcinus mediterraneus much before WSSV outbreaks were reported in Asia [13]. However, in experimental infection studies, WSSV was not able to develop in Mediterranean crab C. menas and this led Corbel and colleagues [4] to suggest that bacilliform viruses morphologically similar to WSSV found in Mediterranean crabs might be either different viruses or at least different strains.…”
Section: Disease Transmission Risk From Shrimps Exported For Human Comentioning
confidence: 99%